Organ-Specific Differential NMR-Based Metabonomic Analysis of Soybean [Glycine max (L.) Merr.] Fruit Reveals the Metabolic Shifts and Potential Protection Mechanisms Involved in Field Mold Infection - Deng, Jun-cai; Yang, Cai-qiong; Zhang, Jing; Zhang, Qing; Yang, Feng; Yang, Wen-yu; Liu, Jiang (Frontiers in Plant Science, 2017)
Prolonged, continuous rainfall is the main climatic characteristic of autumn in Southwest China, and it has been found to cause mildew outbreaks in pre-harvest soybean fields. Low temperature and humidity (LTH) stress during soybean maturation in the field promotes pre-harvest mildew, resulting in damage to different organs of soybean fruits to different extents, but relatively little information on the resistance mechanisms in these fruits is available. Therefore, to understand the metabolic responses of soybean fruits to field mold (FM), the metabonomic variations induced by LTH were characterized using proton nuclear magnetic resonance spectroscopy (1H-NMR), and the primary metabolites from the pod, seed coat and cotyledon of pre-harvest soybean were quantified. Analysis of FM-damaged soybean germplasms with different degrees of resistance to FM showed that extracts were dominated by 66 primary metabolites, including amino acids, organic acids and sugars. Each tissue had a characteristic metabolic profile, indicating that the metabolism of proline in the cotyledon, lysine in the seed coat, and sulfur in the pod play important roles in FM resistance. The primary-secondary metabolism interface and its potential contribution to FM resistance was investigated by targeted analyses of secondary metabolites. Both the seed coat and the pod have distinct but nonexclusive metabolic responses to FM, and these are functionally integrated into FM resistance mechanisms.